2015
DOI: 10.3171/2014.9.spine1412
|View full text |Cite
|
Sign up to set email alerts
|

Progressive restoration of spinal sagittal balance after surgical correction of lumbosacral spondylolisthesis before skeletal maturity

Abstract: OBJECT Spinopelvic alignment is crucial in assessing an energy-efficient posture in both normal and disease states, such as high-displacement developmental spondylolisthesis (HDDS). The overall effect in patients with HDDS who have undergone local surgical correction of lumbosacral imbalance for the global correction of spinal balance remains unclear. This paper reports the progressive spontaneous improvement of global sagittal balance following surgical correction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The results of this study indicated that the sagittal parameters, such as the SLA, LL and SP improved in both groups postoperatively compared with preoperatively. Previous studies have indicated that effective reduction of slip can improve postoperative sagittal spinal balance [27] The maintenance of sagittal spinal balance is crucial for ensuring postural stability and minimizing energy consumption [28] . According to these findings, we can infer that ULIF surgery can improve local and regional sagittal balance.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated that the sagittal parameters, such as the SLA, LL and SP improved in both groups postoperatively compared with preoperatively. Previous studies have indicated that effective reduction of slip can improve postoperative sagittal spinal balance [27] The maintenance of sagittal spinal balance is crucial for ensuring postural stability and minimizing energy consumption [28] . According to these findings, we can infer that ULIF surgery can improve local and regional sagittal balance.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery for high-grade spondylolisthesis (HGS) has the potential to improve the health-related quality of life (HRQoL) 1 . There is also evidence supporting the central role of pelvic balance in the postural control and biomechanics for HGS 2–8 . Achieving adequate postoperative balance is associated with improved HRQoL 9,10 …”
mentioning
confidence: 99%
“…1 There is also evidence supporting the central role of pelvic balance in the postural control and biomechanics for HGS. [2][3][4][5][6][7][8] Achieving adequate postoperative balance is associated with improved HRQoL. 9,10 In addition to the abnormal pelvic morphology characterizing HGS, 11,12 the local deformity at the lumbosacral junction can lead to an unbalanced pelvis.…”
mentioning
confidence: 99%